School education and citizen awareness as guarantors of e preservation of historical and cultural heritage against its destrution and plunder - Bonilla Martos, Antonio Luis (2022)
After centuries of deterioration, loss, theft and destruction of world historial and cultural heritage, there are now national and international standards that seek to safeguard the world’s cultural heritage, however, experience has made us see that these are insufficient if they are not accompanied by educational policies for preservation, protection and conservation of this heritage at the school level, and public awareness campaigns about its importance.